Menganalisis Instrumen Penilaian Pembelajaran Matematika pada Materi Segi Empat Sekolah Menengah Pertama Negeri 1 Dompu - Baharudin, Baharudin (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2015)
The purpose of this study was to describe the usefulness of the instruments of assessment in learning mathematics material covered, any Barriers faced by teachers of mathematics in assessment Instruments and devised alternative solutions to consider in drawing up the instrument for the assessment of attitudes, knowledge and skills. The research approach used in this research is descriptive research is qualitative exploration. The results showed that the teacher makes an instrument of systematic assessment and runtun if seen on the plan of implementation of the learning on the syllabus, the RPP and the Synod of the teacher. But on the other hand that the results of this study explained that teacher assessment tests are instruments devised only to the alleviation of material being taught, then reserved only focused on numbers, not many questions are structured to stimulate the mindset of students where students are required to familiarise problem-solving, so the thinking skills of students both at a high level, critical, creative, and solving the problem is not to obtrusive, only play on numbers alone.